2020
DOI: 10.1038/s41598-020-69451-8
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic transcriptomic sex differences in human endothelial cells at birth and in adults are associated with coronary artery disease targets

Abstract: Sex differences in endothelial cell (EC) biology may reflect intrinsic differences driven by chromosomes or sex steroid exposure and gender differences accumulated over life. We analysed EC gene expression data from boy-girl twins at birth and in non-twin adults to detect sex differences at different stages of life, and show that 14-25% of the EC transcriptome is sex-biased. By combining data from both stages of life, we identified sex differences that are present at birth and maintained throughout life, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 63 publications
3
42
0
Order By: Relevance
“…In fact, HUVECs undergo in vitro angiogenesis, produce NO, and respond to shear stress, hyperglycemia, and inflammatory stimuli, thus recapitulating human disease pathophysiology. In addition, sex-dependent differences in the gene expression and functional properties have been shown in male and female HUVECs by us and other groups [ 12 14 , 17 , 18 , 70 ], indicating HUVECs as a suitable model for studying cellular biological sex and increasing the translational value of basic research. Nevertheless, whether and through which mechanisms HUVEC dimorphic properties are lifelong conserved and regulated in adult male and female ECs still need to be deeper investigated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, HUVECs undergo in vitro angiogenesis, produce NO, and respond to shear stress, hyperglycemia, and inflammatory stimuli, thus recapitulating human disease pathophysiology. In addition, sex-dependent differences in the gene expression and functional properties have been shown in male and female HUVECs by us and other groups [ 12 14 , 17 , 18 , 70 ], indicating HUVECs as a suitable model for studying cellular biological sex and increasing the translational value of basic research. Nevertheless, whether and through which mechanisms HUVEC dimorphic properties are lifelong conserved and regulated in adult male and female ECs still need to be deeper investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, whether and through which mechanisms HUVEC dimorphic properties are lifelong conserved and regulated in adult male and female ECs still need to be deeper investigated. However, a transcriptome analysis comparing HUVECs to adult human ECs has very recently shown that more than 250 genes are concordantly differentially expressed between sexes at birth and in adults [ 70 ], thus further supporting the use of HUVECs as a valuable model for basic research on the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Using twin pairs to study sex differences in transcriptome, Hartaman and colleagues observed that HUVECs from twins of different sexes (male/female) had greater differences in their transcriptome (2528 differentially expressed gene versus 79 in the comparison boy–boy versus girl–girl twins) than HUVECs from twins of the same sex (both male/male and female/female pairs). Females in boy/girl twins showed higher activation of endothelial pathways (endothelial to mesenchymal transition, hypoxia and nuclear factor-kappa B signaling), while males had significantly higher expression of Myc targets, oxidative phosphorylation and mTOR signaling [ 143 ]. Interestingly, some of the detected sex differences were maintained throughout life, confirming that sexual dimorphism starts in utero [ 143 ].…”
Section: Sex Differences In -Huvecs and Huaecsmentioning
confidence: 99%
“…Females in boy/girl twins showed higher activation of endothelial pathways (endothelial to mesenchymal transition, hypoxia and nuclear factor-kappa B signaling), while males had significantly higher expression of Myc targets, oxidative phosphorylation and mTOR signaling [ 143 ]. Interestingly, some of the detected sex differences were maintained throughout life, confirming that sexual dimorphism starts in utero [ 143 ].…”
Section: Sex Differences In -Huvecs and Huaecsmentioning
confidence: 99%
“…Directly after placental delivery, the umbilical cord was stored in phosphate buffered saline (PBS) solution (pH 7.2;) at 4 °C. HUVECs isolation occurred preferably within 12 h, but always within 24 h after placental delivery as described [ 18 ]. Umbilical cords from n = 8 control and n = 12 FGR cases were collected.…”
Section: Methodsmentioning
confidence: 99%